Self-Diffusion and Microstructure of Some Ionic Liquids in Bulk and in Confinement - Filippov, Andrei (Luleå tekniska universitet, Kemiteknik, 2016)
An ionic liquid (IL) is a salt, which usually is in the liquid state at normal temperature and pressure. The properties of ILs can be adjusted for various processes and applications by choosing different combinations of ions. Similar to other salts, ILs contain only ions with positive (cations) and negative (anions) charges in equal proportions. However, to prevent solidification, ions in ionic liquids usually contain bulky organic chemical groups, which, apart from electrostatic interactions, promote other types of interactions between ions, such as: (i) van-der-Waals interactions; (ii) hydrogen bonding; (iii) - stacking, etc., depending on the particular chemical structure of the ions. All these interactions, in combination, may lead to formation of specific microstructures in ILs, which may vary with temperature caused by changing thermal rotational and translational energies of the ions. Ions in these microstructures may have preferential orientations relative to each other, maintain anisotropic properties similar to those in liquid crystals or, in some specific cases, may even separate into microscopically organised liquid phases. Therefore, the dynamics of ILs may also be dependent on their microstructure. In many practical applications ionic liquids are placed on surfaces or in confinements. Solid surfaces introduce extra forces, which may be specific to the charge of the ions or/and to functional groups in the ILs. The geometry and interactions of ions in confinements or/and pores of materials may also disrupt specific bulk microstructures of ILs. Both confinement effects and interactions of ions with surfaces are manifested in the translational dynamics of the ions. One of the most direct and informative methods to study translational dynamics of ILs is pulse-field-gradient nuclear magnetic resonance (PFG-NMR).In this thesis the results of PFG-NMR studies on a few classes of ILs are reported: (i) the historically “standard” (since Walden’s discovery in 1914) ionic liquid, the ethylammonium nitrate (EAN) and (ii) halogen-free orthoborate-based phosphonium, imidazolium and pyrrolidinium ILs with varied structure and lengths of alkyl chains in cations, and varied structures of orthoborate anions. These ILs were studied in bulk at different temperatures, and also in confinements, such as between parallel glass and Teflon plates and in mesoporous Vycor glass. It was found that diffusion coefficients of cations and anions in EAN, phosphonium and pyrrolidinium orthoborate ILs in bulk are different, but according to the standard Stocks-Einstein model, they correspond to diffusion of ions in homogeneous liquids. A change in the chemical structure of one of the ions results in a change in both the diffusion coefficient of the oppositely charged ion and the activation energy of diffusion for both ions in an IL. Similar effects were observed from the chemical shifts and diffusion coefficients measured by NMR for imidazolium orthoborate ILs dissolved in polyethylene glycol solutions, in which imidazolium cations strongly interact with PEG molecules, further affecting the diffusion of orthoborate anions via electrostatic interactions. A liquid-liquid phase separation was suggested for a few phosphonium and pyrrolidinium bis(mandelato)borate ILs, in which a divergence of diffusion coefficients and activation energies of diffusion for cations and anions was detected at temperatures below ca 50 °C. In addition, a free-volume theory was invoked to explain the dependences of density of ILs on the alkyl chain length in cations.It was also found that for a phosphonium bis(salicylato)borate IL confined in 4 nm mesoporous Vycor glass the diffusion coefficients of ions increase by a factor of 35! This phenomenon was explained by the dynamic heterogeneity of this IL in micropores and empty voids of the Vycor glass. For EAN IL in confinements between glass and Teflon plates, the diffusion of ethylammonium cations and nitrate anions is significantly anisotropic, i.e. slower in the direction of the normal to the plates and faster along the plates compared to diffusion of the ions in bulk. A plausible explanation of this PFG NMR data is that EAN forms layers near polar and non-polar solid surfaces. A similar phenomenon, to a lesser extent, was also observed for phosphonium cations of bis(mandelato)borate, bis(salicylato)borate and bis(oxalato)borate confined between glass plates. The results of these studies may have implications in modeling tribological performance, i.e., friction and wear reduction for contact pairs of different materials lubricated by various classes of ionic liquids. === För godkännande; 2016; 20160420 (andfil)